Psychological Pain among Divorced women in Ramallah and Al-Bireh Governorate: Psychological Pain among Divorced women - Brighieth, Mohammed; Rimawi, Omar (Humanities & Social Sciences Reviews, 2022)
Purpose of the study: This study aimed to assess the psychological pain level among divorced women in Ramallah and Al-Bireh Governorate based on various variables. Methodology: The researchers used a descriptive approach to achieve the study goals. The study's sample consisted of (67) divorced women as the researchers used the affordable method to choose using the participants. They also used the Person correlation coefficient with the total score of the instrument to test the instrument's validity. The results showed that all of the questionnaire's items had statistical significance. Findings: The current study's findings revealed a moderate psychological pain level among divorced women in Ramallah and Al-Bireh Governorate, with a ratio of (70.2%). The results showed no statistically significant differences and differences in the means of the participants' responses due to the study's variables (age, academic level, duration of marriage, occupational status, and post-divorce Period). Applications of this study: The researchers expected to apply the research in centers, institutions, and societies focusing on issues for divorced women for psychological and social rehabilitation programs through activities aimed at enhancing their self-confidence. Novelty/Originality of this study: As a result, divorce is a threatening, frightening, and troubling factor for women that causes stress and frustration, particularly in the early post-divorce years.